Literary tourism: authenticity and memory - Ferreira, Ana (2024)
The concern with the authenticity of the tourist experience and the role of literary tourism as a proposal for the interpre-tation and enjoyment of the cultural heritage of a destination are subjects increasingly debated in tourism literature. Thegoal of this article is to contribute to this debate through a literature review focused on the role that literary tourism mayplay in the development of more original and differentiating tourism proposals which contribute to the disseminationand affirmation of the authenticity of the local heritage, preserving the memory of the past and, consequently, the localidentity. The aim was to develop a starting point for an exploratory research on the role that literary tourism plays in theenjoyment of authentic experiences between local communities, their history and tourists/visitors.